Взаємозв'язки інтенсивності забруднення атмосферного повітря та розповсюдженості вроджених вад серця у дітей Запорізької області - Каменщик, Андрій Володимирович; Іванько, Олег Григорович; Каменщик, А. В.; Иванько, О. Г.; Kamenshchyk, A. V.; Ivanko, O. G. (My University, 2013)
У роботі показаний диференційований вплив 14 основних забруднювачів атмосферного повітря у Запорізький області на розповсюдження вроджених вад серця у дітей. Вивчено 1821 випадок ВВС у районах та 5 найбільших містах регіону. Виявлена наявність тісних кореляційних зв’язків загальних викидів у атмосферне повітря із ДМПП, відкритою артеріальною протокою (ВАП), стенозом аорти та легеневої артерії, клапанних та неклапанних комбінованих вроджених вад серця. При цьому більшість кореляцій стосувалася металів та їх сполук, СО, СО2, неметанових легкоокислювальних сполук, а при стенозі аорти спостерігалися допоміжні зв’язки з аміаком SO2, суспендованими твердими частками та сажею. Найбільші внески у розповсюдження таких ВВС, як стеноз аорти, неклапанні та клапанні комбіновані вади серця мали SO2 та NO2, а у ізольовані клапанні дефекти, ВАП, стеноз легеневої артерії - суспендовані тверді частки та сажа відовідно. Виявлені диференційні впливи забруднювачів атмосферного повітря у Запорізькій області на розповсюдженість ВВС різних типів можуть бути як підтвердженням різного походження цих вад серця, так і слугувати основою до їх селективної профілактики. В работе показано дифференцированное воздействие 14 основных загрязнителей атмосферного воздуха на распространенность врожденных пороков сердца у детей Запорожской области. Изучен 1821 случай ВПС по районам и 5 крупнейшим городам региона Установлено наличие тесных корреляционных связей общих выбросов в атмосферу с ДМПП, открытым артериальным протоком (ОАП), стенозом аорты и легочной артерии, клапанных и неклапанных комбинированных врожденных пороков сердца. При этом большинство корреляций касалось металлов и х соединений, СО,СО2, неметановых легкоокисляемых соединений, а при стенозе аорты имели место также дополнительные корреляции с аммиаком, SO2, суспендированными твердыми частицами и сажей. Наибольшие вклады в распространенность таких ВПС как стеноз аорты, неклапанные и клапанные комбинированные пороки сердца имели SO2 и NO2, а в изолированные клапанные дефекты, ОАП, стеноз легочной артерии – суспендированные твердые частицы и сажа соответственно. Выявленные дифференцированные воздействия загрязнения атмосферного воздуха в Запорожской области на распространенность различных типов ВПС могут являться как подтверждением различного происхождения данных пороков сердца, так и служить основой для их селективной профилактики. There is a substantial attention given recently to the influence of anthropogenic factors upon children health. Contributions of ambient air pollutants to the occurrence of allergic, neurological, cardiovascular diseases and congenital anomalies have the important role as well. In the same time an inequality of air pollution by quantity and composition in different regions of Ukraine is emphasizing. On the other hand, due to intensive growth and development children are the most vulnerable group for the impacting of environmental factors to their health state. In this relation, taking into account multifactorial origin of congenital heart diseases which mainly resulted from environmental genotoxic and endogenous genetic factors the differential studying of air pollution influences to certain types of CHD is arising. The objective of the study is to establish interrelation between ambient air pollution intensity and congenital heart diseases occurrence in children of Zaporizhzhya region as well as to detect the possible risks for this pathology among the population exposed to the air pollutants for the long period. At the first phase of study official information about 14 main ambient air pollutants such as total air pollution, metals and compounds, N20, NO2, H2S, ammonia, SO2 and compounds, SO2, CO, CO2, methane, non- methane fast oxidizing compounds, suspended particulate matters and soot has been analyzed. At the second stage a database about regional distribution of 1821 CHD case has been developed. Using correlations and multiple regression approach the data were processed with Statictica 6.0 program. It has been established the general influence of air pollution is characterized by positive correlations with ASD, PDA, aortic and pulmonary artery stenosis, valve and non - valve combined heart defects. Most of correlations are related to metals, CO, CO2 and non methane oxidizing compounds but in aortic stenosis an additional ones are admitted with the ammonia, SO2, suspended particulate matters and soot. Largest inputs in aortic stenosis, non-valve and valve combined defects have been produced by SO2 and NO2 as major pollutants in the region but they have produced no inputs to isolated valve defects, PDA and pulmonary artery stenosis in which the largest inputs are linked to particulate matters and soot. Thus, on the one hand, the detected differential effects of air pollutants on the prevalence of different CHD types reflect the different origin of these defects when exposing to more toxic components of pollution and, on the other hand, can serve as a basis to selective prevention of congenital heart defects.
Взаимосвязи интенсивности загрязнения атмосферного воздуха и распространенности врожденных пороков сердца у детей Запорожской области
Interrelation between ambient air pollution intensity and congenital heart diseases occurrence in children of Zaporizhzhya region
Keywords: вроджені вади серця; діти; забруднювачі атмосферного повітря; диференційні впливи; Запорізька область; врожденные пороки сердца; дети; загрязнение атмосферного воздуха; дифференцированные воздействия; Запорожская область; congenital heart defects; children; ambient air pollution; differential impact; Zaporizhzhya region